Predictive Success and Non-Individualist Models in Social Science. (March 2017) - Lauer, Richard
The predictive inadequacy of the social sciences is well documented, and philosophers have sought to diagnose it. This paper examines Brian Epstein's recent diagnosis. He argues that the social sciences treat the social world as entirely composed of individual people. Instead, social scientists should recognize that material, non-individualistic entities determine the social world, as well. First, I argue that Epstein's argument both begs the question against his opponents and is not sufficiently charitable. Second, I present doubts that his proposal will improve predictive success for the social sciences, which I support with Edith Penrose's resource-based theory of the firm.